WOMEN'S REPRESENTATION IN FOLK LITERATURE OF UTTARAKHAND - Negi, Pallavi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines the multifaceted representation of women in the folk literature of Uttarakhand, exploring their roles as nurturers, rebels, heroines, and victims within folk songs, tales, and traditions. Through a qualitative approach, it analyzes how these narratives reflect and shape gender dynamics, societal norms, and cultural identity. The study also delves into ecofeminist themes, highlighting women’s connection to nature and their contributions to environmental sustainability. Furthermore, it investigates the impact of modernization, migration, and digitalization on the portrayal and preservation of women-centric narratives. The findings underscore the enduring significance of Uttarakhand’s folk literature in reflecting societal values while emphasizing the evolving roles and agency of women in both traditional and contemporary contexts.